2017
DOI: 10.1016/j.jss.2017.05.101
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin effect is enhanced by sphingosine-1-phosphate signaling antagonist in breast cancer

Abstract: Background Doxorubicin is one of the most commonly used chemotherapeutic drugs for breast cancer; however, its use is limited by drug resistance and side-effects. We hypothesized that adding FTY720, a sphingosine-1- phosphate (S1P) receptor functional antagonist, to doxorubicin would potentiate its effects by suppression of drug-induced inflammation. Materials and Methods The Cancer Genome Atlas (TCGA), GEO datasets, and NCI-60 panel were used for gene expressions and gene set enrichment analysis (GSEA). E07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 73 publications
0
50
0
Order By: Relevance
“…Some references providing clinical evidence to show the S1P axis involved in the therapies resistant of tumors. In Katsuta et al48 study, it suggested that the expression of sphingosine kinase 1 tended to be higher in doxorubicin‐resistant human cancer and cell lines. In Nagahashi et al49 recent study, they used FTY720 to target SPHK1/S1P/S1PR1 axis and suggested that this pathway is associated with obesity‐related inflammation and breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 93%
“…Some references providing clinical evidence to show the S1P axis involved in the therapies resistant of tumors. In Katsuta et al48 study, it suggested that the expression of sphingosine kinase 1 tended to be higher in doxorubicin‐resistant human cancer and cell lines. In Nagahashi et al49 recent study, they used FTY720 to target SPHK1/S1P/S1PR1 axis and suggested that this pathway is associated with obesity‐related inflammation and breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 93%
“…To identify the features of the low DMT1-expressing HCC, which have worse DFS after liver resection, GSEA was conducted based on the 50 hallmark gene sets. 44 Intriguingly, oxidative phosphorylation and glycolysis gene sets were found to be enriched in DMT1 low tumors in addition to DNA repair and reactive oxygen species gene sets (Table 2). Respiratory metabolism-related gene sets, such as glycolysis (Normalized enrichment score [NES] ¼ À1.547, P ¼ 0.022), oxidative phosphorylation (NES ¼ À2.166, P < 0.001), which generates adenosine triphosphate (ATP) using pyruvate, a product of glycolysis, and reactive oxygen species pathway (NES ¼ À1.766, P ¼ 0.011), were enriched in the low DMT1expressing HCC among 50 hallmark gene sets ( Fig.…”
Section: Dmt1 Expression Level Inversely Associates With Oxidative Phmentioning
confidence: 99%
“…GSEA was performed comparing DMT1 high and low patients utilizing the Java GSEA implementation version 3.0 provided by the Broad Institute (http://software.broadinstitute.org/ gsea/index.jsp) as described previously. [42][43][44][45]…”
Section: Gene Set Enrichment Analysismentioning
confidence: 99%
“…Combination of doxorubicin with FTY720 resulted in reduced inflammation and synergistic suppression of cancer growth in vitro and in vivo. Furthermore, in an obesity breast cancer model where mice were fed a high-fat diet, this combination therapy was also efficacious [82]. …”
Section: Pp2a Activationmentioning
confidence: 99%